Modeling Sectoral Stock Indexes Volatility: Empirical Evidence from Pakistan Stock Exchange - Chimrani, Charan Raj; Ahmed, Farhan; Panjwani, Vinesh Kumar (International Journal of Economics and Financial Issues, 2018)
Modeling volatility in financial markets is one of the factors that results in direct impact and effect on pricing, risk and portfolio management. This study aims to examine the volatility of stock indices in PSX that include; volatility clustering, fat tails and leptokurtosis behavior. To achieve the objective, ADF Unit root test has been performed to check the stationarity and it was concluded from the results that series were stationary at 1st difference. Series taken for this research consists of 11 sectors which includes Commercial Banks (DCB), Cement (DCEM), and Chemicals (DCHEM). Fertilizers (DFER), Investment Banks and Investment Companies (DIB), Insurance (DINS), Oil and Gas (DOG), Power generation and distribution (DPGD), Refinery (DREF) and Technology and Communication (DTC). This study applies; ARCH, GARCH, and EGARCH to evaluate the behavior of share price volatility of Pakistan Stock Exchange (PSX) covering the period from Jan. 1 2009 through Dec.31 2016. The main findings suggests that EGARCH or GARCH models are the best fit for all the series as decision making criterion Akaike Information Criterion (AIC) and Schwarz Criterion(SC) are least in these models. Keywords: Volatility, PSX, Stock Index, ARCH JEL Classification: C22